Status of insecticide susceptibility in Anopheles gambiae s.l. from malaria surveillance sites in The Gambia - Betson, Martha (BioMed Central, 2009)
BACKGROUND: Vector control is an effective way of reducing malaria transmission. The main vector control methods include the use of insecticide-treated bed nets and indoor residual spraying (IRS). Both interventions rely on the continuing susceptibility of Anopheles to a limited number of insecticides. However, insecticide resistance, in particular pyrethroid-DDT cross-resistance, is a challenge facing malaria vector control in Africa because pyrethroids represent the only class of insecticides approved for treating bed nets and DDT is commonly used for IRS. Here baseline data are presented on the insecticide susceptibility levels of malaria vectors prior to The Gambian indoor residual spraying intervention programme. METHODS: Anopheles larvae were collected from six malaria surveillance sites (Brikama, Essau, Farafenni, Mansakonko, Kuntaur and Basse) established by the National Malaria Control Programme and the UK Medical Research Council Laboratories in The Gambia. The mosquitoes were reared to adulthood and identified using morphological keys and a species-specific polymerase chain reaction assay. Two- to three-day old adult female mosquitoes were tested for susceptibility to permethrin, deltamethrin and DDT using standard WHO protocols, insecticide susceptibility test kits and treated papers. RESULTS: All Anopheles mosquitoes tested belonged to the Anopheles gambiae complex. Anopheles arabiensis was predominant (54.1%), followed by An. gambiae s.s. (26.1%) and Anopheles melas (19.8%). Anopheles gambiae s.s. and An. arabiensis were found at all six sites. Anopheles melas was recorded only at Brikama. Mosquitoes from two of the six sites (Brikama and Basse) were fully susceptible to all three insecticides tested. However, DDT resistance was found in An. gambiae from Essau where the 24 hours post-exposure mortality was <80% but 88% for permethrin and 92% for deltamethrin. CONCLUSION: This current survey of insecticide resistance in Anopheles provides baseline information for monitoring resistance in The Gambia and highlights the need for routine resistance surveillance as an integral part of the proposed nation wide IRS intervention using DDT.